(untitled) (Journal of Hama University, 2026)
The poultry industry is considered one of the most important and reliable sources for obtaining relatively cheap animal protein all over the world. One of the most important production problems facing this industry is the infection with bacterial and viral factors. Therefore, those factors that inhibit the reproductive process must be effectively controlled. Avian cholera is a highly contagious disease of global economic importance resulting from infection with Pasteurella multocida bacteria. In this study, the extent of the spread of Pasteurella multocida in sick and healthy chickens in the central region of Syria was determined. Samples of the lungs, trachea, and heart were collected from (200) Sick chickens included (180) commercial (mothers and broilers) and (20) domestic (local) chickens. Samples were also collected from (100) apparently healthy chickens, including (90) commercial (mothers and broilers) and (10) domestic (local) chickens. This was done from ten geographically different breeding sites to isolate Pasteurella multocida. Samples were collected from each bird from the trachea, lungs, and heart. Then culture was performed on the blooded agar culture and MacConky agar . Suspected bacteria were also examined under the microscope after staining them with Giemsa stain to confirm their bipolar characteristic , Then biochemical tests were conducted on samples suspected of bacterial culture. The prevalence rate was Which we obtained from the culture results on the differential cultures (5.6)%,while the prevalence rate was obtained by biochemical tests (4.3)% ,Then confirmatory identification was performed using polymerase chain reaction (PCR), and the prevalence rate was (3.6)%.